Low-level laser therapy: an efficient supplement to treatments of vulvar Lichen sclerosus to improve quality of life - Pia Kirstine Berthelsen; Sidsel Eb Ipsen; Mohammed R. Khalil (Journal of Obstetrics and Gynaecology)
Background Lichen sclerosus (LS) is a chronic, inflammatory disease of the genital and extra genital skin, causing pruritus, soreness, pain and dyspareunia. The aim of this study was to investigate whether Low Level Laser Therapy (LLLT) can improve the quality of life in women with Lichen sclerosus (LS) and insufficient topical treatment.Methods In a descriptive prospective observational study conducted between 02.01.2016 and 08.01.2018, we included 100 women with LS with insufficient topical treatment because of poor response of symptoms. All participants received ten LLLT treatments (808 nm and 500 mW) over a period of 8 weeks. The first four treatments were planned as two treatments per week. The remaining six treatments were planned as once a week. A Danish health-related quality of life tool (HRQoL test) monitored the effect.Results A total of 94 patients completed the study, median age of 62 [InterQuartile Range 53–69]. There was a statistically significant improvement in seven of the eight domains of the HRQoL test after ten LLLT. We found the results of DoloTest to be statistically significant in all of the groups except for smoking (p < 0.094).Conclusions LLLT treatment can improve the quality of life in women with LS.